Pertimbangan Hakim Menjatuhkan Pidana Terhadap Turut Serta dalam Tindak Pidana Pencemaran Nama Baik Melalui Media Sosial (Studi Kasus Putusan Pengadilan Negeri Padang Nomor 700/Pid.Sus/2020/PN Pdg) - Adrian Bima Putra; Elwi Danil; A. Irzal Rias (UNES Law Review, 2023)
In the practice of law enforcement against criminal acts of defamation through social media in the jurisdiction of the Padangv District Court, we can see the judge's decision to sentence the defendant to prison for violating the ITE Law. The judge in decision Number 700/Pid.Sus/2020/PN Pdg on behalf of Robby Putra Eryus, nicknamed Robby, was legally and convincingly proven to have committed a violation against. Article 27 paragraph (3) of the ITE Law in conjunction with Article 56 paragraph of the Criminal Code. This research is normative juridical research using secondary data. This research is a descriptive analysis. The research results show that: 1. The judge's consideration in imposing a conditional sentence on the defendant was based on the consideration that the defendant's actions were carried out not only for the defendant's personal interests but also for the interests of society, which were related to humanity, in this case because of community service. 2. The perspective of justice assesses that the criminal penalties imposed on those involved are in accordance with the views and principles of justice, especially according to Rawls.